2010
DOI: 10.4061/2010/864724
|View full text |Cite
|
Sign up to set email alerts
|

In Stent Restenosis Predictors after Carotid Artery Stenting

Abstract: Purpose. The long-term efficacy of carotid artery stenting is debated. Predictors of stent restenosis are not fully investigated. Our aim was to assess the incidence of long term restenosis after CAS and to identify some predictors of restenosis. Methods. We retrospectively selected 189 treated patients and we obtained the survival Kaplan-Meier curves for overall survival, for freedom from stroke or death and from restenosis. To correlate clinical, radiological, and procedural variables to stent restenosis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…3,24 However, this hypothesis has not been supported by large evidence. Our study, as well as others in the literature, 2,25,26 confirmed that diabetic patients have similar restenosis rates compared with nondiabetic patients, whichever treatment was applied to treat carotid stenosis.…”
Section: Discussionsupporting
confidence: 93%
“…3,24 However, this hypothesis has not been supported by large evidence. Our study, as well as others in the literature, 2,25,26 confirmed that diabetic patients have similar restenosis rates compared with nondiabetic patients, whichever treatment was applied to treat carotid stenosis.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous studies that reported that restenosis is most common in the first year post CAS and the risk of restenosis decreases in subsequent years 8 9. Groschel et al 6 reported in their systematic review that 71% of patients had restenosis in the first year after CAS.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that the intramural wall stress from the stent caused more damage to the vessel wall and subsequent excessive repair, ultimately leading to ISR. 26 Therefore, choosing a stent of the appropriate size may effectively reduce the blood flow dynamics and mechanical interference on the vessel wall, thereby reducing the incidence of ISR.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that patients with long lesions and a high percentage of residual stenosis have high rates of restenosis. 26,27 In our study, we divided 39 patients with imaging follow-up into 2 groups based on the median length of the vascular lesions (5.39 mm). Patients whose vascular lesions were longer than 5.39 mm had a much higher incidence of ISR (53% versus 15% for patients with a lesion length of 5.39 mm; P Ïœ .05).…”
Section: Discussionmentioning
confidence: 99%